PERANCANGAN CHATBOT UNTUK INFORMASI PENERIMAAN MAHASISWA BARU PADA STMIK KHARISMA MAKASSAR - Marline Wijaya; Junaedy; Hamdan Arfandy (KHARISMA Tech, 2019)
The purpose of this research is to design and create chatbots that can answer general questions about information on New Student Admission at STMIK KHARISMA Makassar. The benefit of this research is to help users get information on New Student Admission at STMIK KHARISMA Makassar. The research begins by designing the ENTITY RELATIONSHIP Diagrams (ERD) and Unified Modeling Language (UML). Then the chatbot is implemented using the LINE Messaging API with the PHP programming language and Codeigniter framework. Whereas for admin system to process chatbot, it is made web-based and implemented with PHP programming language and CodeIgniter framework and Bootstrap Admin Klorofil template. The program is tested by using Black Box Testing method. Based on the results of the research it can be concluded that the author has succeeded in designing and creating a chatbot that can help users to get information on New Student Admission at STMIK KHARISMA Makassar.